Efficiency in teaching modern intensive methods - Rakhimova Muhabbat Ergashevna (Zien Journals, 2022)
This article defines the principles and their impact on foreign language learners through an intensive teaching methodology.
Keywords: principle; integral; suggestive-cybernetic; concentrations